mHealth Pilot Study: Text Messaging Intervention to Promote HPV Vaccination - Lee, Hee Yun (Am J Health Behav, 2016)
OBJECTIVES: To test the feasibility and efficacy of a culturally-tailored mobile health intervention designed to increase knowledge about, intent to obtain, and receipt of the HPV vaccine. METHODS: A 7-day text message HPV intervention was developed using a quasi-experimental research design for 30 Korean-American women. RESULTS: Participants demonstrated significant increases in knowledge of HPV with an intent to get vaccinated within one year, and 30% of participants received the first dose of the HPV vaccine. CONCLUSIONS: Mobile health technology could be a promising tool in reducing the cancer burden for underserved populations.